Mecanismos de defesa e controle genético da resistência por antixenose à Liriomyza sativae em genótipos de meloeiro - Araújo, Ariana Veras de (2019)
The search for sources of resistance to the leafminer in melon germplasm (Cucumis melo L.) has led to the identification of resistant genotypes by antixenosis and/or antibiosis. However, for the best use of these genotypes, it is important to elucidate the genetic inheritance and defense mechanisms involved in resistance. Thus, the aim of this study was to characterize melon genotypes by associating leaf traits with resistance to Liriomyza sativae Blanchard and to elucidate genetic control of antixenosis resistance in the CNPH 94-244 accession. For this purpose, CNPH 11-1077, CNPH 11-1072 and CNPH 94-244 accessions, previously identified as resistant, and the insect-susceptible commercial hybrids Goldex and Iracema were evaluated for antixenosis (number of leafminers) and antibiosis (larval and pupal viability) resistance to the leafminer. Colorimetric (L*a*b* system) and morphological (internal leaf anatomy, quantification and trichome typing) analyzes were performed to establish associations between leaf traits and insect resistance. Additionally, two cross-structured populations between CNPH 94-244 and the commercial hybrids Goldex and Iracema were simultaneously submitted to L. sativae infestation, in cage and in the field. Regarding insect resistance, the following response variables were evaluated: leafminers and pupae per plant (cage infestation) and subjective grade and number of leafminers (field infestation). Genetic studies were based on the averages and variances of parents (P1 and P2), branch generations (F1 and F2) and backcrosses (BC1 and BC2). CNPH 94-244 accession was less preferred by L. sativae than hybrids. CNPH 11-1072 and CNPH 11-1077 accessions showed antibiosis for reducing larval and pupal viability. CNPH 94-244 accession resistance was associated with less intense green color (a*) and density of glandular trichomes. In the CNPH 11-1072 and CNPH 11-1077 accessions leaf characters associated with resistance were the thickness of palisade and spongy parenchyma. The susceptibility of 'Iracema' accession showed that the average of leafminers is associated with the abundance of tector trichomes. In 'Goldex' accession the average of leafminers was associated with high luminosity (L*) and more intense yellow color (b*). Based on the F1 generation averages of the populations CNPH 94-244 x 'Goldex' and CNPH 94-244 x 'Iracema', there was non-additive allelic interaction in the genetic control of evaluated variables. The complete model was adequate to explain the inheritance of variables, and the additive effect was the most important. The heritability in restricted sense was high for leafminers (cage infestation) and number of leafminers (field infestation) in F2 of the CNPH 94-244 x 'Goldex' and CNPH 94-244 x 'Iracema' crosses, respectively. In population of CNPH 94-244 x 'Goldex', by gene number, genetic inheritance is oligogenic for subjective notes and polygenic for leafminers and pupae per plant and number of leafminers. At the cross between CNPH 94-244 x 'Iracema', inheritance is polygenic for leafminers and pupae per plant, and oligogenic for subjective grade and number of leafminers. Therefore, association of leaf characters with resistance is genotype dependent. Iracema hybrid is a susceptibility pattern to L. sativae and CNPH 94-244 accession is the most promising for antixenosis resistance. And the genetic inheritance of antixenosis resistance to L. sativae in CNPH 94-244 is quantitative in nature, with a predominance of additive effects.